CT screening for lung cancer: Importance of emphysema for never smokers and smokers. Issue 1 (April 2015) - Henschke, Claudia I.; Yip, Rowena; Boffetta, Paolo; Markowitz, Steven; Miller, Albert; Hanaoka, Takaomi; Wu, Ning; Zulueta, Javier J.; Yankelevitz, David F.; ,
Highlights: Lung cancer prevalence increased when emphysema was identified on low-dose CT scan. Never smokers with CT evidence of emphysema are at the same risk of lung cancer as a smoker. Prevalence of lung cancer was similar among smokers and never smokers below age 50. Abstract: Purpose: To address the prevalence of lung cancer in high and low-risk people according to their smoking history, age, and CT findings of emphysema. Methods: We reviewed the baseline low-dose CT scans of 62, 124 current, former and never smokers, aged 40–90 to determine the prevalence of lung cancer. We performed logistic regression analysis of the prevalence of lung cancer to determine the odds ratio (OR) for emphysema, conditionally on age, female gender, and ethnicity. Results: The prevalence of lung cancer was 1.4% (95% CI: 1.3–1.6) for current smokers, 1.1% (95% CI: 1.0–1.2) for former smokers, and 0.4% (95% CI: 0.3–0.6) for never smokers. Emphysema was identified in 28.5% (6, 684), 20.6% (5, 422), and 1.6% (194) of current, former, and never smokers, respectively. The prevalence of lung cancer among current smokers was 1.1% for those without emphysema vs. 2.3% for those with emphysema (odds ratio [OR] 1.8; 95% confidence interval [CI]: 1.4–2.2) and the corresponding difference for former smokers was 0.9% vs. 1.8% (OR: 1.7; 95% CI: 1.3–2.2), and for never smokers, it was 0.4% vs. 2.6% (OR: 6.3; 95% CI: 2.4–16.9). Conclusions: Identification of emphysema in low-dose CT scans increases the risk of lung cancer and is important in determining follow-up of current, former, and never smokers.